Skin-Resident Antigen-Presenting Cells: Instruction Manual for Vaccine Development - Fehres, Cynthia M.; Garcia-Vallejo, Juan J.; Unger, Wendy W.; Van Kooyk, Yvette (Frontiers in Immunology, 2013)
The induction of antigen-specific effector T cells is driven by proper antigen presentation and co-stimulation by dendritic cells (DCs). For this reason strategies have been developed to instruct DCs for the induction of CD4+ and CD8+ T cell responses. Since DCs are localized, amongst other locations, in peripheral tissues such as the skin, new vaccines are aiming at targeting antigens to DCs in situ. Optimal skin-DC targeting in combination with adequate adjuvant delivery facilitates DC maturation and migration to draining lymph nodes and enhances antigen cross-presentation and T cell priming. In this review we describe what DC subsets populate the human skin, as well as current vaccination strategies based on targeting strategies and alternative administration for the induction of robust long-lived anti-cancer effector T cells.